Strategi Pembelajaran Bahasa Arab Yang Mudah Dipahami - Rachma Isna Noora; Faisal Hendra (Publikasi Indonesia, 2023)
Arabic is becoming a very important language in a global context, as an official language in many countries and as an international language. However, the use of Arabic still often faces obstacles in communication effectiveness due to language misuse. Therefore, this study aims to identify acceptable and easy-to-understand Arabic translation strategies. The research method used is a qualitative research method with document review techniques through old manuscripts or previous research results related to this research. The results showed that an acceptable and easy-to-understand Arabic translation strategy involves several steps, such as understanding context, choosing the right words, using simple sentences, using synonyms, and understanding Arabic grammar well. In translation, the principles of self-instruction are also applied, including the use of dictionaries, practice by speaking, reading, and writing in Arabic.